Pendekatan Desain Kolaboratif dalam Upaya Mengembangkan Program Ekstrakurikuler Sekolah Dasar - Anton, Anton; Hamim Muhamad Ilyas; Muhamad Salman Naufal Firdaus (Yayasan Literasi Sains Indonesia, 2025)
Islamic Religious Education (PAI) has a very important role in shaping the character and morals of students. Improving the quality of PAI teachers is a crucial issue in the context of education in Indonesia, considering the challenges faced by PAI teachers, such as less varied teaching methods and low student motivation. This study aims to analyze the factors that influence the improvement of the quality of PAI teachers, including pedagogical competence, mastery of technology, professionalism, and strengthening the character and ethics of teachers. The results of the study indicate that good pedagogical competence allows teachers to design interesting and effective learning. The use of information and communication technology (ICT) also has a positive impact, increasing the appeal of materials and student involvement. In addition, improving teacher professionalism through ongoing training and strengthening the character of PAI teachers as role models in morals is also very important. Support from schools and government policies is needed to create a conducive environment for professional development teachers. With a comprehensive approach, it is hoped that the quality of Islamic religious education can improve, thus producing a young generation that has noble and competent morals.